TECHNOLOGIES OF EQUIPMENT DIAGNOSIS IN THE TUBE PRODUCTION - A. N. Kattsyn (Литьë и металлургия, 2013)
The possibilities of complex diagnostic measures that reduce the risks of accidents related to equipment breakdown in the tube production are considered.